Gender, women and word in fawziyyah al-Bakr's hayatu min waraqin (2016)
The emergence of gender in Arabic literary writing in the contemporary period is partly traceable to the popularity of women's movement all around the world. This does not, however, mean that before today the Arab literary landscape had neglected issues which border on women's right, the girl-child, women's sexuality, marital obligation among others. In fact, Arabic literary writing since the classical period exemplifies an extremely strong patronage, by poets and prose writers of men and women subjects. A reading of the works of lmru'u'1-Qays, al-Khansa', al-MutannabT among others compels this conclusion. This paper investigates the concept of gender in general and gender in Arab land and Saudi Arabia in particular. In this paper, I briefly analyse the work of a female writer; Fawziyyah Al-Bakrto showcase female literary writers in the Kingdom of Saudi Arabia, which are all but ignored in literary scholarship.